Pengaruh Penerapan Metode Quantum Kauny terhadap Peningkatan Kemampuan Tahfidz Qur’an Siswa di SD IT Cendekia Darussalam - Afriandi, Dicki; Salami, Salami; Huwaida, Huwaida (Tadabbur: Jurnal Peradaban Islam, 2024)
Problems that become obstacles in carrying out the tahfidz Qur'an program at SD IT Cendekia Darussalam, thereby disrupting the improvement of the quality and ability of tahfidz Qur'an of students at school, include the lack of enthusiasm and motivation of students in memorizing the Qur'an, the deposit for memorizing was not fluent, students could not understand the meaning of their memorization and also the use of learning media and the choice of methods were inappropriate which cause the problems with the quality of students' memorization.This study was aimed to find out (a) how high the quality of students' memorization of the Qur'an is after implementing the quantum kauny method at SD IT Cendekia Darussalam. (b) the effect of applying the quantum kauny method on improving students' tahfidz Qur'an abilities at SD IT Cendekia Darussalam. The method used in this research was quantitative experimental method with a Quasi Experimental pretest posttest control group design. The samples in this study were students of class VI AL-Munadi and class VI Al-Munawwir. Data collection techniques in this research consisted of tests, documentation, observation and interviews. The results of the research show that there is a difference in test results using the Quantum Kauny method in pretest and posttest using the conventional method, this is proven by the "t" test and the results of hypothesis testing in class VI Al-Munawwir obtained tcount > ttable namely 13.066 > 2.07387 and significance value (2-tailed) < 0.05. then the test results in class VI Al-Munadi obtained tcount > ttable, namely 2.369 > 2,045 and the significance value (2-tailed) < 0.05, and the N-Gain test from the results of the N-gain analysis in the Experiment class was 0.33 medium category and control class 0.-12 low category. So it can be concluded that the use of the quantum kauny method has an effect on increasing the ability of tahfidz Qur'an students at SD IT Cendekia Darussalam because Ha is accepted and Ho is rejected